Continental-scale effects of nutrient pollution on stream ecosystem functioning. - Woodward,G; Gessner,MO; Giller,PS; Gulis,V; Hladyz,S; Lecerf,A; Malmqvist,B; McKie,BG; Tiegs,SD; Cariss,H; Dobson,M; Elosegi,A; et al. (Science, 2012)
Excessive nutrient loading is a major threat to aquatic ecosystems worldwide that leads to profound changes in aquatic biodiversity and biogeochemical processes. Systematic quantitative assessment of functional ecosystem measures for river networks is, however, lacking, especially at continental scales. Here, we narrow this gap by means of a pan-European field experiment on a fundamental ecosystem process--leaf-litter breakdown--in 100 streams across a greater than 1000-fold nutrient gradient. Dramatically slowed breakdown at both extremes of the gradient indicated strong nutrient limitation in unaffected systems, potential for strong stimulation in moderately altered systems, and inhibition in highly polluted streams. This large-scale response pattern emphasizes the need to complement established structural approaches (such as water chemistry, hydrogeomorphology, and biological diversity metrics) with functional measures (such as litter-breakdown rate, whole-system metabolism, and nutrient spiraling) for assessing ecosystem health.